Avaliação da competição entre a espécie nativa Geophagus brasiliensis (Quoy & Gaimard, 1824) e a exótica Oreochromis niloticus (Linnaeus, 1758) confinadas em tanques em diferentes densidades - Biagioni, Renata Cassemiro (Universidade Federal de São Carlos, 2015)
In Brazil, species introduction in freshwater ecosystems has become an important topic in conservation ecology, as it is one of the main causes of biodiversity loss. Invasive species benefiting from the lack of natural enemies outside their original geographic distribution might represent a highly competitive pressure to the native species sharing the same resources of the invaded areas and may lead to changes in the abundance and richness of natural communities. In this sense, for a better understanding of these relationships, it is possible to study experimentally the interactions between invasive and native species evaluating competition effects. So, the objective of this study was to assess, through an experimental approach, if there is intraspecific and interspecific competition between two cichlid fish: a native species, the cará Geophagus brasiliensis and the exotic Nile tilapia Oreochromis niloticus. The objective was to examine if there is differential growth and feeding under different fish densities in consortium or separated. The experiment was conducted in Setor de Aquicultura do Polo Regional Vale do Paraíba - APTA Regional in the municipality of Pindamonhangaba, from March to June 2014. In order to assess the intraspecific competition of each species due to increased density and, comparing them with interspecific competition when the two species coexist in the same tank, five treatments with four replicas were considered. Fish diet studies suggest that there was no intraspecific and interspecific competition for food in this experiment. Despite the morphological similarities between the two fish species, the weight gain is evident and it can be assigned to the treatment itself. Intraspecific competition was not detected, as there was no significant decrease in the average weight gain for both species with increasing density of individuals of the same species. As for the interspecific competition, the results suggest that space availability may have been the main factor of dispute between species, since there was no significant change in diet and the consortium of these species benefited O. niloticus in much higher proportion than G. brasiliensis.
The competition assessment between native species Geophagus brasiliensis (Quoy & Gaimard, 1824) and the exotic Oreochromis niloticus (Linnaeus, 1758) confined in tanks at different densities
Keywords: Ecologia marinha; Marine ecology; Peixes - comportamento; Fishes - behavior; Invasão biológica; Biological invasion; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS; CIENCIAS EXATAS E DA TERRA::OCEANOGRAFIA::OCEANOGRAFIA BIOLOGICA